ONE-POT SYNTESIS OF MENTHOL FROM CITRONELLAL : APPLICATION OF CITRONELLA OIL - Indri Badria Adilina, Tasrif, Joddy Arya Laksmono dan Egi Agustian (Jurnal Teknologi Industri Pertanian, 2007)
ABSTRACTSynthesis of menthol (C10H20O) from citronellal (C10H18O) has been performed by a one-pot process. The process was conducted in a 250 mL capacity autoclave with acidified natural zeolite and Raney Nickel as catalysts at temperature 120°C, pressure 5 bar, and variation of time 1-8 hours. Natural zeolite and Raney Nickel were placed in the autoclave and it was found that the cyclisation and hydrogenation reaction to form menthol could undergo in the same reactor. FTIR Analysis showed peak formation at 3346.50 cm-1 indicating –OH group was formed. Result of 1H-NMR and 13C-NMR analysis reports chemical shifts at δ=71.53 ppm and  δ=4.05 ppm. Gas chromatography analysis showed that the conversion was 80% with concentration of menthol about 68% (v/v). Keywords : menthol, citronellal, one-pot reaction, citronella oil.